(untitled) (Revista Logos Ciencia & Tecnología, 2019)
This paper presents a SALBP (simple assembly line balancing problem) problem, where n tasks are performed on manual workstations, located along a production line. The problem is studied using the variations SALBP-1, SALBP-2 and SALBP-F; the latter is treated as a bi-objective model, in order to evaluate possible feasible solutions of the combination of stations and process times. The three variations are solved with the use of heuristic methods and analytical methods, to conclude on the complexity of the problem and the efficiency of the proposed solutions.